2020
DOI: 10.1007/s00228-020-03043-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, preventability, and causality of adverse drug reactions at a university hospital emergency department

Abstract: Purpose To investigate the characteristics of ADRs in patients admitting at the emergency room of a tertiary hospital. Methods We collected the patient records of 1600 emergency room visits of a university hospital in 2018. The patient files were studied retrospectively and all possible ADRs were identified and registered. Patient characteristics, drugs associated with ADRs, causality, severity, preventability, and the role of pharmacogenetics were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
(81 reference statements)
0
10
0
3
Order By: Relevance
“…These data are in line with other studies on the subject. 8,10,12,14,16,17 Gastrointestinal bleeding site was a predictor of hospitalization, probably due to its higher severity and the need for diagnostic or therapeutic endoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in line with other studies on the subject. 8,10,12,14,16,17 Gastrointestinal bleeding site was a predictor of hospitalization, probably due to its higher severity and the need for diagnostic or therapeutic endoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent examples demonstrate the potential for improved patient outcomes as a result of integration of pharmacogenetics and electronic medical records, for example, in tacrolimus dose selection 196 , evaluation of the clinical relevance of arrhythmia-related rare genetic variants 197 , and in characterizing associations between genotype and adverse drug effects 198 . Interestingly, a very recent analysis of adverse drug reactions from medical records of a university hospital emergency department found that only two of 125 adverse drug events observed in a 6-month period may have been prevented by pharmacogenetics testing 199 , further highlighting the importance of accounting for both genetics and patient history in successfully predicting patient outcomes. Significant advancements have been made in extracting (and de-identifying) relevant data from patient medical records, including the descriptive text contained in clinician notes that allow valuable insights into A c c e p t e d M a n u s c r i p t adverse outcomes, off-label drug use, and nuances of disease that are challenging to directly capture from electronic records 200 .…”
Section: Future Perspectives Of Pharmacogenomic Implementation In Primary Carementioning
confidence: 99%
“…In der zwischen 2012 und 2018 durchgeführten, italienischen MEREAFaPS-Studie wurden bei 337 arzneimittelinduzierten Todesfällen zu 40 % Antikoagulanzien oder Thrombozytenfunktionshemmer als ursächlich angesehen [16]. Eine gleichfalls hohe Inzidenz von unerwünschten Arzneimittelreaktionen aus der ATC-Klasse (anatomisch-therapeutisch-chemische Einordnung) der Antithrombotika fand sich neben der von Zytostatika auch in einer retrospektiven, monozentrischen Studie, die im Jahr 2018 in der Notaufnahme des Universitätsklinikums Helsinki durchgeführt wurde [17]. Zu ähnlichen Ergebnissen kommen auch Daten aus den portugiesischen und deutschen Pharmakovigilanzsystemen bei älteren Patienten sowie Studienergebnisse aus Metaanalysen [18][19][20][21].…”
Section: Häufigkeit Von Tödlichen Und Nichttödlichen Unerwünschten Arzneimittelwirkungenunclassified